Kolaborasi Pemerintah dalam Upaya Pencegahan Penyalahgunaan Narkoba di Kota Medan - Putri Nurul Afifah Bangun; Februati Trimurni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the problem of drug abuse in Medan City, which has 145 drug-prone and drug-alert sub-districts, the largest number in North Sumatra Province. To reduce this number, the government is implementing preventative measures through a collaborative approach involving the National Narcotics Agency of North Sumatra Province, the National Unity and Politics Agency of North Sumatra Province, and the Family Welfare Movement Team of North Sumatra Province with support from Non-Governmental Organizations, particularly in the Anti-Drug Family Resilience Program. This study used a descriptive qualitative method with informants from the National Narcotics Agency (BNN), the National Unity and Politics Agency (Kesbangpol), the PKK Movement Team, and the PEKA Association. Data were collected through interviews, observation, and documentation. The results show collaboration between stakeholders, such as the socialization of the dangers of drugs held jointly by the BNN, PKK, and PEKA. However, this program faces obstacles such as low community participation, limited human resources, and a limited budget. Therefore, private sector involvement, increased human resource capacity, and stronger regional regulations are needed to strengthen drug abuse prevention efforts in Medan City.